Multi-Product Firms, Endogenous Sunk Costs, and Gains from Trade through Intra-Firm Adjustments - Michael Irlacher (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
In this paper, I investigate welfare gains associated with trade induced intra-firm adjustments of multi-product firms. To disentangle the welfare gains, I split up the R&D portfolio of a multi-product firm into three different channels: i) product innovation, ii) investments in the degree of product differentiation, and iii) process innovation. Trade integration enables firms to exploit economies of scale as innovation requires upfront development costs and encourages firms to spend more on R&D. I derive the indirect utility function and show that consumers bene.t from this behavior through a larger product range (love of variety) which is also more differentiated (love of diversity). Furthermore, a larger market is associated with technology upgrading. The resulting cost savings are passed on to consumers, leading to welfare gains from lower prices.
urn:nbn:de:bvb:19-epub-21023-2
Keywords: F12; F61; L25; 330; International Trade; Multi-Product Firms; Gains from Trade; R&D; Cannibalization Effect; Product Differentiation